Non-β-Blocking Carvedilol Analog, VK-II-86, Prevents Ouabain-Induced Cardiotoxicity. - Gonano, Luis Alberto (2018)
Background It has been shown that carvedilol and its non β-blocking analog, VK-II-86, inhibit spontaneous Ca2+ release from the sarcoplasmic reticulum (SR). The aim of this study is to determine whether carvedilol and VK-II-86 suppress ouabain-induced arrhythmogenic Ca2+ waves and apoptosis in cardiac myocytes. Methods and Results: Rat cardiac myocytes were exposed to toxic doses of ouabain (50 µmol/L). Cell length (contraction) was monitored in electrically stimulated and non-stimulated conditions. Ouabain treatment increased contractility, frequency of spontaneous contractions and apoptosis compared to control cells. Carvedilol (1 µmol/L) or VK-II-86 (1 µmol/L) did not affect ouabain-induced inotropy, but significantly reduced the frequency of Ca2+ waves, spontaneous contractions and cell death evoked by ouabain treatment. This antiarrhythmic effect was not associated with a reduction in Ca2+ calmodulin-dependent protein kinase II (CaMKII) activity, phospholamban and ryanodine receptor phosphorylation or SR Ca2+ load. Similar results could be replicated in human cardiomyocytes derived from stem cells and in a mathematical model of human myocytes. Conclusions Carvedilol and VK-II-86 are effective to prevent ouabain-induced apoptosis and spontaneous contractions indicative of arrhythmogenic activity without affecting inotropy and demonstrated to be effective in human models, thus emerging as a therapeutic tool for the prevention of digitalis-induced arrhythmias and cardiac toxicity.